A comparative assessment of metal bioavailability using various universal extractants for smelter contaminated soils: Novel insights from mineralogy analysis. (20th September 2022) - Xu, Da-Mao; Fu, Rong-Bing
Abstract: Smelter contaminated soils represent a recurrent hazard for human health, because of the possibility of potentially hazardous elements entering the soil–plant–human systems. This exploratory study was aimed to evaluate the potential bioavailability of anthropogenic elements based on the integrated analysis of mineralogical and geochemical approaches. The present results showed that Cd, Pb and Zn were enriched in soils around smelters. The bioavailable metal concentrations fluctuated greatly across a range of extractant and soil types, as well as metal contamination levels. Cd, Cu, Mn, Pb and Zn were identified as more bio-available elements by various universal extractants, and their extractability patterns could be better described by the second order kinetic model. The mineralogical investigation indicated that after bioavailability extraction, the soil particles in the residues still presented O, Al, Si, and Fe as the main elements. The combined results of the geochemical and mineralogical analysis demonstrated that the complexing extractant (0.5 mol/L CH3 COONH4 and 0.02 mol/L EDTA) as more aggressive extractant was able to extract metal cations embedded within silicate lattices, and also by partially dissolving metal bound carbonate minerals, oxides and iron oxohydroxides. Therefore, the potential risks from Cd, Cu, Mn, Pb and Zn needed to be seriously concerned, due to their possible translocation from the rhizosphere soils into the local agricultural crops and residents. This study provided the valuable information about the risk assessment studies of smelter contaminated soils. Graphical abstract: Image 1 Highlights: Anthropogenic elements such as Cd, Cu, Mn, Pb and Zn were identified using various universal extractants. 0.5 mol/L CH3 COONH4 and 0.02 mol/L EDTA showed the higher metal extractability. The release kinetic data of more bio-available elements were better fitted using the second order kinetic models. The integrated analysis of mineralogical characterization provided new insight into metal bioavailability.